OXYGEN THERAPY MANAGEMENT IN THE TREATMENT OF PATIENTS WITH NEW CORONAVIRUS INFECTION - Ликстанов, Михаил Исаакович; Курпе, Елена Евгеньевна; Ромасюк, Анна Владимировна; Каменева, Евгения Александровна; Сергиенко, Ирина Сергеевна; Мозес, Вадим Гельевич; Мозес, Кира Борисовна; Рудаева, Елена Владимировна; Елгина, Светлана Ивановна (Medicine in Kuzbass, 2021)
The experience of solving the problems of the functioning of engineering systems at the stages of launching and direct operation of a redesigned covid hospital is presented.